FURFURILASI PADA KAYU TUSAM (Pinus merkusii Jungh. et de Vr.) DAN MANGIUM (Acacia mangium Willd.) - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Wood specimens of tusam (Pinus merkusii Jungh. et de Vr.) and mangium (Acaciamangium Willd.) were air-dried to approximately16-18% moisture content. One group of the specimens was further oven-dried ttJ reach moisture content of 6-8%. Furfurylation was undertaken by soaking wood specimens/or 24 hours in a 98%.furfuryl alcohol solution containing 0.35% (vlv) of ZnCl2 as catalyst. Furfurylated specimens were then cured at 1 OO°C for 48 hours. Wood characteristics observed in this study include dimentional stability, hardness, compression strength and shear strength.Test results showed that the initial wood specimens of tusam had a higher radial but a lower tangential swelling rates than those specimens of mangium. Furfurylation could improve wood dimentional stability of both species by more than 90% on tusam and 75% on mangium.Values of hardness, compression strength and shear strength of tusam were markedly lower than mangium. After furfurylation, however, tusam had a greater hardness than mangium. Furfurylation could increase hardness, compression strength and shear strength of tusam by more than 94%, 83% and 76% respectively. A lower wood mechanical improvements were encountered with the mangium specimens.